Regional order : Indonesia's shifting redlines? - Syailendra, Emirza Adi (2022)
The emergence of AUKUS appears to have triggered a reaction from Indonesia that is typically subtle. Are the powers involved in the changing regional order, Australia included, able to read between Jakarta's (red)lines?